2012
DOI: 10.1155/2012/306818
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility Training and Functional Ability in Older Adults: A Systematic Review

Abstract: Background. As indicated in a recent systematic review relating to Canada's Physical Activity Guidelines for Older Adults, exercise interventions in older adults can maintain or improve functional abilities. Less is known about the role of flexibility in the maintenance or improvement of functional abilities, and there currently does not exist a synthesis of the literature supporting a consensus on flexibility training prescription. Purpose. To systematically review the effects of flexibility-specific training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
9

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 29 publications
1
56
0
9
Order By: Relevance
“…A recent and very comprehensive systematic review showed that flexibility can be improved by specific training; however, according to these authors, there are several constraints in the 22 studies analyzed that preclude obtaining a more definitive answer, regarding if these benefits are transformed in better functional outcomes for older adults (Stathokostas et al 2012). Although, by reading their data, indeed, it can be identified that most studies are relatively short (few weeks long) and that flexibility was most often assessed by multicomposite tests, such as sit-andreach, which, in our opinion, may compromise the interpretation of the information.…”
Section: Discussionmentioning
confidence: 99%
“…A recent and very comprehensive systematic review showed that flexibility can be improved by specific training; however, according to these authors, there are several constraints in the 22 studies analyzed that preclude obtaining a more definitive answer, regarding if these benefits are transformed in better functional outcomes for older adults (Stathokostas et al 2012). Although, by reading their data, indeed, it can be identified that most studies are relatively short (few weeks long) and that flexibility was most often assessed by multicomposite tests, such as sit-andreach, which, in our opinion, may compromise the interpretation of the information.…”
Section: Discussionmentioning
confidence: 99%
“…It is hypothesized that similar positive results could be achieved in other major muscle groups through proper stretching interventions. However, a recent systematic review indicated that there is no definitive conclusion on the optimal flexibility program for older adults (Stathokostas et al 2012).…”
Section: Typementioning
confidence: 99%
“…As indicated in a recent systematic review by our group [1], there is conflicting information regarding both the relationship between flexibility training interventions and functional outcomes and the relationship between improved flexibility and daily functioning; health benefits have not yet been established. The comparison of studies in this area to provide a prescription of the flexibility is complicated by the variety of limb ranges of motion studied, testing procedures utilized, and methods of assessing physical activity levels.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of the present study was to examine the cross-sectional age-related differences in flexibility in a large sample of independently living adults aged 55–86 years with varying activity levels. The recent systematic literature review identified the lack of an established relationship between improved flexibility and daily functioning and health benefits [1]. As such, a secondary purpose of the present study was to describe any relationships of physical activity levels and of functional outcomes (specifically walking), with flexibility measures.…”
Section: Introductionmentioning
confidence: 99%